Evaluation of relationship between endodontic access cavity types and secondary mesiobuccal canal detection - Gokhan Saygili; Banu Uysal; Bawar Omar; Elif Tarim Ertas; Huseyin Ertas (BMC, 2018)
Abstract Background The aim of this study was to evaluate the relationship between Endodontic Access Cavity (EAC) types with MB2 canal detection ratio in the upper first molars. Methods A total of 60 roots of extracted human maxillary first molars were selected. All teeth were prepared with Point EAC (PEAC), Conservative EAC (CEAC) and Traditional EAC (TEAC) respectively. After each group were completed, extra canal was searched. Preoperative and postoperative tooth weigh was calculated using precise scale. McNemar's chi-square test and a paired test significant difference were used for statistical analyses. Results The EAC types statistically were changed of tooth tissue loss quantity (p = 0.000). MB2 detection rate of CEAC (%53,3) and TEAC (%60) are higher than statistically that of PEAC (%31.6) (p < 0.05). 8 teeth MB2 canal was detected only with the CBCT images. Conclusions In upper molars, CEAC seems reasonable in terms of detected the MB2 canal and removed hard tissue.